A informatividade como recurso de argumentação na produção escrita - Fonseca, Frederico Gustavo de Lima (2015)
Seeking to contribute to discussions about the text production of teaching in high school this work deals with the informativeness as a resource in the construction of the written text of the argument. After observing a constant lack of data considered sufficient in the texts presented by the students in the classroom, we try to bring the problem some referrals that can assist beyond current teachers, who are in training. Structured in four chapters, this work deals with theoretical framework about language, language and text; opinion article and didactic situation in the first. In the second, the record of practiced intervention to test the didactic situations designed to ensure that students understand the need to acquire sufficient information to build a good text. In the last two, we have, respectively, the analysis of written and rewritten of opinion articles requested in the classroom. The practice has developed into a private school in the city of Recife / PE in a third-year middle class formed by forty-two students with ages that vary from sixteen to eighteen. As theoretical support to develop the work, we rely mainly on three authors: Antonio Marcuschi, Ingedore Koch and Irandé Antunes. These authors have guided us in order that we put into question the hypothesis that the most informative was the text, it would be the best argument.